1999
DOI: 10.1152/jappl.1999.87.2.801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine on neuromuscular function

Abstract: This double-blind, repeated-measures study examined the effects of caffeine on neuromuscular function. Eleven male volunteers [22.3 +/- 2.4 (SD) yr] came to the laboratory for control, placebo, and caffeine (6 mg/kg dose) trials. Each trial consisted of 10 x 1-ms stimulation of the tibial nerve to elicit maximal H reflexes of the soleus, four attempts at a maximal voluntary contraction (MVC) of the right knee extensors, six brief submaximal contractions, and a 50% MVC held to fatigue. Isometric force and surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
157
3
22

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(199 citation statements)
references
References 32 publications
17
157
3
22
Order By: Relevance
“…No significant increases from PRE were seen in glucose concentrations for both S (5.30 6 0.40 mmolÁL 21 ) and P (5.50 6 1.12 mmolÁL 21 ). Lactate concentrations were significantly increased IP for both S (17.8 6 5.7 mmolÁL ), and remained increased from PRE throughout the 30-minute recovery period, but no significant group differences were observed.…”
Section: Resultsmentioning
confidence: 82%
“…No significant increases from PRE were seen in glucose concentrations for both S (5.30 6 0.40 mmolÁL 21 ) and P (5.50 6 1.12 mmolÁL 21 ). Lactate concentrations were significantly increased IP for both S (17.8 6 5.7 mmolÁL ), and remained increased from PRE throughout the 30-minute recovery period, but no significant group differences were observed.…”
Section: Resultsmentioning
confidence: 82%
“…Incomplete activation of the ankle plantarflexors is commonly observed and voluntary activation levels of 90 to 99% have typically been reported [31,35,68] . In comparison with other muscles, relatively low levels of quadriceps femoris activation (85-95%) have frequently been observed [21,23,40,41,69,70,71,72,73,74,75] .…”
Section: Maximal Isometric Contractionsmentioning
confidence: 99%
“…Three factors should be borne in mind when interpreting the available evidence. Firstly, in a number of the earlier studies voluntary activation of the elbow flexors [7,95] and quadriceps femoris muscles [8,96,97] appeared to be complete prior to training although subsequent experiments employing more sensitive techniques have shown that the same muscles are typically not fully activated [14,15,17,21,66,73] . Secondly, when activation deficits have been observed, dynamic resistance training was employed whilst the tests of voluntary activation were isometric [71,98] .…”
Section: 3 the Influence Of Resistance Trainingmentioning
confidence: 99%
“…Reductions in RPE are caused by caffeine restricting adenosine from binding to the adenosine receptors in the brain, thus blocking the inhibitory action of the adenosine on the central nervous system (12,31). Caffeine also increases motor unit recruitment and drive to the muscle that enhances muscular force production (25). A greater force production facilitated by caffeine ingestion might therefore have contributed to improved sprint performance in the CHO-C trial.…”
Section: Discussionmentioning
confidence: 99%
“…As an adenosine antagonist (11), caffeine moves freely across the blood-brain barrier, with the central nervous system (CNS) its primary target (12). Effects include reduced perceptions of effort and pain (9,27), increased central drive (25) and, to a lesser extent, increased muscle force and endurance (39).…”
Section: Introductionmentioning
confidence: 99%